Plant Drought Tolerance Enhancement by Trehalose Production of Desiccation-Tolerant Microorganisms - Vílchez, Juan I.; García-Fontana, Cristina; Román-Naranjo, Desireé; González-López, Jesús; Manzanera, Maximino (Frontiers in Microbiology, 2016)
A collection of desiccation-tolerant xeroprotectant-producing microorganisms was screened for their ability to protect plants against drought, and their role as plant growth-promoting rhizobacteria was investigated in two different crops (tomato and pepper). The most commonly described biochemical mechanisms for plant protection against drought by microorganisms including the production of phytohormones, antioxidants and xeroprotectants were analyzed. In particular, the degree of plant protection against drought provided by these microorganisms was characterized. After studying the findings and comparing them with results of the closest taxonomic relatives at the species and strain levels, we propose that trehalose produced by these microorganisms is correlated with their ability to protect plants against drought. This proposal is based on the increased protection of plants against drought by the desiccation-sensitive microorganism Pseudomonas putida KT2440, which expresses the otsAB genes for trehalose biosynthesis in trans.